Rekonstruksi Fikih Lingkungan Berbasis Ekoteosentris dalam Penanggulangan Sampah Laut - Rahmatul Qadri; Azman Arsyad; Lomba Sultan (Media Hukum Indonesia (MHI), 2026)
The growing problem of marine debris indicates that technical and regulatory approaches alone have been insufficient to address the escalating ecological crisis. This condition suggests that the root of the problem lies not only in inadequate environmental governance but also in an anthropocentric paradigm that regards nature merely as an object of exploitation. This article aims to reconstruct environmental fiqh based on an ecotheocentric paradigm as an Islamic legal framework for addressing marine debris. This study employs a library research design with a normative-philosophical approach. Data were analyzed using descriptive-analytical methods by integrating the Qur’an, Hadith, maq??id al-shar??ah, classical fiqh, and contemporary environmental thought. The findings reveal that reconstructing environmental fiqh from an ecotheocentric perspective shifts the orientation of Islamic law from human-centered protection toward safeguarding marine ecosystems as a divine trust (am?nah). This reconstruction is reflected in the expansion of the legal object of protection to include marine ecosystems, the extension of ecological responsibility to individuals, communities, industries, and the state, and the formulation of Jar?mah Bi’iyyah Ba?riyyah as a normative category for marine pollution subject to ta?z?r sanctions oriented toward ecological restoration. These findings contribute to the development of contemporary environmental fiqh while offering a more responsive Islamic legal paradigm for addressing ecological crises and promoting ecological justice.